2014
DOI: 10.1590/s1982-21702014000200025
|View full text |Cite
|
Sign up to set email alerts
|

Using a least squares support vector machine to estimate a local geometric geoid model

Abstract: In this study, test-region global positioning system (GPS) control points exhibiting known first-order orthometric heights were employed to obtain the points of plane coordinates and ellipsoidal heights by using the real-time GPS kinematic measurement method. Plane-fitting, second-order curve-surface fitting, backpropagation (BP) neural networks, and least-squares support vector machine (LS-SVM) calculation methods were employed. The study includes a discussion on data integrity and localization, changing refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Для обчислення регіональної моделі геометричного геоїда здебільшого використовують штучну нейронну мережу [Kao, 2014] та розклад у ряд за степеневими функціями Eteje et al, 2018 IJASRE, 4 (8), 206-214. Haines G. V. (1985).…”
Section: основні розрахункиunclassified
“…Для обчислення регіональної моделі геометричного геоїда здебільшого використовують штучну нейронну мережу [Kao, 2014] та розклад у ряд за степеневими функціями Eteje et al, 2018 IJASRE, 4 (8), 206-214. Haines G. V. (1985).…”
Section: основні розрахункиunclassified
“…Based on the results of this research, the MLPNN model was found to be more accurate than the other methods tested. Another soft-computing method is represented by the least square support vector machine (LS-SVM), which is the least squares formulation of the support vector machine (SVM) and has been applied to detect a geoid model (Zaletnyik et al, 2008;Kao et al, 2014;Kaloop et al, 2018). In addition to ANN and LS-SVM methods, the ANFIS approach has also been used by geodesy researchers in geoid modeling (Akyilmaz et al, 2008;Yilmaz, 2010;Yılmaz and Arslan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the development of suitable local geoid undulation models by applying various fitting methods to measurements of ellipsoidal height h and leveling orthometric height H obtained using global positioning systems (GPSs) (Odera et al, 2014;Abdalla et al, 2011;Abdalla and Fairhead, 2011;Akcin and Celik, 2013;Abdalla, 2009;Featherstone et al, 2004;Kao et al, 2014 ;Kao, 2006;Kotsakis and Sideris, 1999;Kao and Bethel, 1992(a); Kao and Bethel, 1992(b) ;Ning, 2015;Lin, 2007;Tranes et al, 2007;Kiamehr, 2006;Ustun and Demirel, 2006;You, 2006;Yang and Chen, 1999). The geoid of each position in a location can be calculated to determine H for each position.…”
Section: Introductionmentioning
confidence: 99%